Giving Olive Oil to Diaper Rash in Infants Aged 6-12 Months in The Work Area Of The Nambo Health Center - Suhartati Suhartati; Isra Wati; Fath Irtaniyah Rahman; La Ode Liaumin Azim (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2023)
Background: Diaper rash is one of the most common skin diseases experienced by infants and toddlers with a high incidence and prevalence. Diaper rash occurs because the cause of diaper rash is fungus and bacteria. Treatment of diaper rash can be done in a non-pharmacological way, one of which is by using olive oil. Objective: The purpose of this study was to determine the effect of giving Olive Oil on diaper rash in infants aged 6-12 months in the working area of the Nambo Health Center. This type of research is a quasi-experimental design with one group pretest-posttest on 16 respondents through total sampling. Result: The results of this study indicate that before administration of olive oil, the most diaper rash in infants was moderate, namely 8 respondents (50%) while after administration of olive oil, diaper rash in infants recovered the most (no diaper rash). Namely 6 respondents (37.5%). Wilcoxon test shows the P value = 0.001 (≤ 0.05). Conclusion: So it can be concluded that there is an effect of giving olive oil to reduce the degree of baby diaper rash.